PERANCANGAN GEOMETRIK JALAN ANTAR KOTA MENGGUNAKAN AUTOCAD CIVIL 3D STUDENT VERSION (STUDI KASUS JALAN MANDEH PROVINSI SUMATERA BARAT) - Ruhdi Faisal; Lulusi Lulusi; Sectioly Sanra (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2021)
The roadway geometric designing must consider as optimal as possible time spent in designing and building a road. This study aims to determine the results of road geometric design using manual calculation methods and calculations by using AutoCAD Civil 3D Student Version 2016 with a case study of St. Mandeh STA 30 + 000 - STA 37 + 000. The design scope consists of horizontal alignment design, superelevation, and vertical alignment. The method used by reference standard of AASHTO 2011, and for criteria design used by Bina Marga 1997 standard. The results of the horizontal alignment design, obtained 6 SCS curves, 3 FC curves, and 5 SS curves. The manual calculation results are the same as the results of AutoCAD Civil 3D calculations for FC curves and SCS curves. For the SS curve, the result difference is 0.2 m. AutoCAD Civil 3D only calculates the superelevation of FC curve and SCS curve, then the calculation of SS curve have done by manual design. In the vertical alignment design there were 4 crest vertical curves and 3 sag vertical curves with a slope of 0.02% - 5.23% approprite the maximum slope requirement of 11%. The length of crest and sag vertical curve Lv approprite the K value requirement for stopping visibility and preceding visibility